Performance Study of the Direct-Coupled Photovoltaic Water Pumping System for the Rural-Isolated Agricultural Region in Iraq - Mahmood hussein salman; Adel A. Obed; Ahmed J. Abid (Journal of Techniques)
The rural-isolated agricultural region in Iraq and some developing countries lack access to electricity, and thus the primarily alternative is to use diesel water pumping systems to irrigate their crops. However, due to a rise in the oil's price on the international market, toxic pollution from burning oil, high maintenance costs, and short lifespans have been challenged to create more viable alternatives. Renewable energy can limit the use of fossil fuels, particularly by using the solar-powered water pumping system. This article aimed at finding an optimal design for a direct-coupled photovoltaic water pumping system in Iraq. The article presents the significant design aspect for an optimal system, such as the groundwater aquifer depth, installation aspect, cost, and irrigation efficiency. The design offers a combination of sprinkler and environmentally sustainable and cost-effective photovoltaic technology to reduce electricity and water use. A deep well to the storage system is adopted with, 40m maximum well depth, 90m3 reservoir, 1200W submersible pump, and 1800 Wp, which can supply water to 12 greenhouses for three days. The yearly results show pumping efficiency is increased up to 42.6%, used water need is achieved at 10950 m3, and unused energy is reduced by 48.8%.